2021
DOI: 10.1155/2021/6616546
|View full text |Cite
|
Sign up to set email alerts
|

Research on Permeability Coefficient of Heterogeneous Geomaterials Based on Digital Images

Abstract: According to the relationship between permeability and porosity of geotechnical materials, a finite element model representing pore and solid particles is generated randomly according to the porosity of a given finite element calculation model. According to Darcy’s law of flow distribution and steady seepage in the finite element random simulation section, the equivalent permeability coefficients at different porosities are calculated, and the relationship between the equivalent permeability coefficient and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Wu and Zhang, (2009) proposed a numerical analysis method for one-dimensional coupling of seepage and deformation of elastic soil. Jia et al (2007) and Liu et al (2021) derived the basic equation of unsteady seepage in unsaturated soil. Zhang et al (2006Zhang et al ( , 2020 calculated the influence of water level decline on slope safety factor under different slopes of soil-water characteristic curves.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Zhang, (2009) proposed a numerical analysis method for one-dimensional coupling of seepage and deformation of elastic soil. Jia et al (2007) and Liu et al (2021) derived the basic equation of unsteady seepage in unsaturated soil. Zhang et al (2006Zhang et al ( , 2020 calculated the influence of water level decline on slope safety factor under different slopes of soil-water characteristic curves.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuji et al (2019) built digital rock models based on CT images and found that the permeability was strongly influenced by mineralization and rock types. Liu et al (2021) utilized a random arrangement of pores and solid particles randomly to develop a finite element model with an equivalent permeability coefficient according to Darcy's equation. Yan et al (2021) applied the lattice Boltzmann method on a constructed three-dimensional (3D) digital rock based on nuclear magnetic resonance (NMR) results and calculated absolute permeability of rock; their results showed that by combining the spectral bulk volume irreducible method with the traditional Coates permeability model, the results correlate well with the NMR data.…”
mentioning
confidence: 99%